Turtles of the midnight moon - Fitzgerald, María José (Alfred A. Knopf, 2023)
Twelve-year-old Abby feels lost after her best friend moves away from New Jersey, so she's excited when her papi plans a work trip to Honduras, and she's given the chance to see his homeland. She meets twelve-year-old Barana, who is committed to protecting the sea turtles that nest on the beach nearby, and Abby soon joins Barana in her mission. When they discover someone is poaching turtle eggs before they can hatch, the girls set out to unmask the thief.